Analisis Rantai Pasok Beras di Desa Tukum Kabupaten Lumajang, Indonesia - Lituhayu Supartiningrum; Yuli Wibowo; Bambang Herry Purnomo (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Rice remains the main staple food in Indonesia and plays a crucial role in ensuring national food security. Nevertheless, traditional rice supply chains often result in unequal distribution of economic benefits among actors and lack support from formal institutions. This study aims to analyze the structure of the rice supply chain, calculate the distribution of value added using the Hayami method, and formulate data-driven improvement strategies in Tukum Village, Tekung District, Lumajang Regency. The research was conducted from January to March 2025 and involved 30 farmers, 5 collectors, and 1 milling enterprise, all selected purposively. Data were obtained through surveys, interviews, and direct observation, and then analyzed quantitatively using Hayami’s value-added framework. The results indicate that the rice supply chain in Tukum Village is linear and dominated by informal relationships, involving four key actors: farmers, collectors, millers, and consumers. Farmers generated the highest value added, amounting to Rp 21,020.38 per kilogram or 50.75% of the output. Collectors contributed Rp 806.82/kg (15.09%), while rice millers added Rp 3,192.55/kg (25.46%). Although farmers contributed the most, their bargaining power remained weak due to dependency on collectors for finance and market access. Millers played a strategic role in product transformation but faced high operational costs, limiting their net margins and efficiency. The findings highlight that strengthening farmer organizations, developing value chain-based financing schemes, and promoting modernization and digitalization are crucial strategies to improve the system. These measures are not only essential for achieving a fairer and more efficient distribution of value added but also for enhancing the resilience of local food systems to support sustainable national food security.